The Role of Ethnicity in Rural Development: A Study on the Distribution of Education and Employment - Zessy Ardinal Barlan; Sampean; Andi Muhammad Agriawan Suryaalim; Sofyan Sjaf; Abdurrahman Harits; Rifaldi Cahyanto; Lukman Hakim; Rajib Gandi; Ahmad Aulia Arsyad; Rizki Budi Utami; Badar Muhammad (Universitas Negeri Semarang, 2026)
Rural development in multi-ethnic areas requires data-driven approaches that precisely capture social inequalities. This study aims to analyze the relationship between ethnicity, educational attainment, and employment sectors in four villages in East Kalimantan, Indonesia: Kutai Lama, Sidomulyo, Sanga-Sanga Muara, and Muara Pantuan. Employing a quantitative approach using the Bayesian Contingency Table method, along with polarisation and ethnic fractionalization indices, this study utilized microdata from 13,007 individuals based on Data Desa Presisi. The findings indicated no statistically significant relationship between ethnicity and educational or employment outcomes (BF10 < 1), thus supporting the null hypothesis. Ethnicity was not significantly correlated with educational attainment or employment type. However, descriptive analysis reveals distinct patterns among ethnic groups, such as a higher concentration of informal sector employment among Bugis and Sundanese, and greater representation in the formal sector among Javanese and Banjar communities. These patterns suggest that complex social dynamics are not necessarily reflected in statistical associations. Polarisation and fractionalization indices further indicate that unmanaged ethnic diversity may exacerbate social inequalities. This study underscores the importance of inclusive microdata-based development strategies. This study contributes to the literature on ethnicity-based rural development, while opening new avenues for exploring the intersectionality of ethnicity, education, and employment in rural Indonesia.